2021
DOI: 10.21037/tlcr-21-265
|View full text |Cite
|
Sign up to set email alerts
|

Defining oligometastatic non-small cell lung cancer: concept versus biology, a literature review

Abstract: In this review, the concept of (synchronous) oligometastatic disease in patients with nononcogene-driven non-small cell lung cancer (NSCLC) will be placed in the context of tumor biology and metastatic growth patterns. We will also provide considerations for clinical practice and future perspectives, which will ultimately lead to better patient selection and oligometastatic disease outcome. Background:The treatment landscape of metastasized NSCLC has moved from "one-size fits all" to a personalized approach. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
1
8
0
1
Order By: Relevance
“…Over the past 30 years oligometastatic NSCLC has been recognized as a unique clinical entity [3][4][5]11,25]. Several retrospective series and some prospective studies have demonstrated the efficacy and safety of aggressive approaches in selected patients with OMD and supported the use of metastasis-directed ablative radiotherapy alone, or in addition to a primary therapy to consolidate all sites of gross disease [26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 30 years oligometastatic NSCLC has been recognized as a unique clinical entity [3][4][5]11,25]. Several retrospective series and some prospective studies have demonstrated the efficacy and safety of aggressive approaches in selected patients with OMD and supported the use of metastasis-directed ablative radiotherapy alone, or in addition to a primary therapy to consolidate all sites of gross disease [26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The definition and management of oligometastatic NSCLC have been incorporated into current guidelines on lung cancer, supporting the use of a definitive treatment with curative intent directed to primary disease and including focal ablation of all sites of oligometastatic involvement [8][9][10][11]. In the pre-immunotherapy era, prospective phase 2 randomized trials have shown an increase in progression free survival (PFS) and overall survival (OS) for oligometastatic patients receiving radiotherapy (RT) as local ablative treatment (LAT) in combination with systemic therapy [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The primary implanted particle in patients treated with RPI was 125 I, and the median number of particle implantation was 1 time (range,1–4 times). Oligometastatic status was defined as a maximum of 5 metastases in 3 organs, but diffuse plasma membrane (meningeal, pleural, pericardial, and mesenteric) or bone marrow metastases were not included in this definition ( 18 ). Based on the peak timing of RT to promote tumor-specific antigen release, we preliminarily explored the optimal timing of immune drug intervention.…”
Section: Methodsmentioning
confidence: 99%
“…These categories included (1) synchronous oligometastatic disease where oligometastasis and the primary tumor are detected concurrently at the time of diagnosis, (2) metachronous oligometastatic or oligo-recurrent disease where oligometastatic lesions are detected three months after the initial diagnosis while the primary tumor is controlled, (3) oligo-progressive metastatic disease where progression after systemic therapy occurs in a limited number of metastases, and (4) oligo-persistent metastatic disease where oligo-metastases persist after systemic therapy [ 18 ]. Nevertheless, a universal definition of oligometastatic disease has not been adopted yet, and discrepancy regarding the number of organs involved, the volume of the metastasis, and the response of the primary tumor persists, in addition to the patient’s performance status and the likelihood of tolerating local ablative therapies [ 3 ].…”
Section: The Current Concept Of Oligometastatic Nsclcmentioning
confidence: 99%
“…Despite the current advances in lung cancer screening, at least 50% of patients with newly diagnosed non-small cell lung cancer (NSCLC) will present with metastatic disease at diagnosis [ 1 ]. Among those patients, approximately 37.5% will present with a limited metastatic state referred to as “oligometastatic” [ 2 ], requiring a multidisciplinary treatment approach with systemic agents combined with potential metastasis-directed local ablative therapies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%